Protection of the right of damage sufferers in the Law on State compensation liability of Viet Nam = Bảo vệ quyền của người bị thiệt hại trong Luật trách nhiệm bồi thường của nhà nước của Việt Nam - Trần, Thị Thu Hằng (2020)
The thesis focuses on analyzing and clarifying theoretical issues about the rights and protecting of the rights of damage sufferers in international law and Vietnamese law in the Law on State compensation liability. Research and practice assessment to protect the right of damage sufferers in the Law on State compensation liability of Viet Nam in the stage from January 01, 2010 up to now. Thereby, proposing a number of solutions to protect the right of damage sufferers in Viet Nam.